Perilaku dan Keterampilan Menyikat Gigi terhadap Timbulnya Karies Gigi pada Anak di Kota Jambi - Sukarsih Sukarsih; Aida Silfia; Muliadi Muliadi (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2019)
Dental and oral health is a health problem that requires comprehensive treatment, because dental problems are of a broad dimension and have wide-ranging impacts including physical, mental and social factors for individuals suffering from dental diseases. The purpose of this study was to determine the factors associated with the emergence of dental caries in children aged 10-12 years at SDN 59 / IV Jambi City in 2019. This research design uses cross sectional. The sampling technique used was random sampling, which was a random sampling technique, with a total sample of 40 people. Measuring instruments used were questionnaires and dental caries observation sheets. Chi square test results that there is a relationship between dental health knowledge with dental caries status (DMF-T) in children aged 10-12 years SDN 59 / IV Jambi city with a value of Sig = 0.028 or p value ≤ 0.05. There is a relationship between maintenance of dental health with dental caries status (DMF-T) in students aged 10-12 years SDN 59 / IV Lotus with a value of Sig = 0.017 or p value ≤ 0.05. There is a relationship between how to brush teeth with dental caries status in students aged 10-12 years SDN 59 / IV Jambi city with a value of Sig = 0.013 or p value ≤ 0.05.